Manufacturing industrial structure and pollutant emission: An empirical study of China - Wang, Zheng; Jia, Haifeng; Xu, Te; Xu, Changqing (Journal of cleaner production, 2018)
This paper describes the relationship between industrial structure and pollutant emissions in a rapidly developing manufacturing-dominated city in China. Using detailed firm survey data, we observed several characteristics in the relationship: Pareto distribution of output value and pollutant emissions by divisions, groups and classes, increased industrial concentration, larger firms and lower pollutant emissions. A negative correlation between industrial concentration and pollutant emission is found, clarified by an analysis of firm size and pollution emissions at the group and class level. Based on the data analysis, this work suggests that upgrade and improvement of industrial structure conducive to the reduction of polluting emissions can only be successful in a unified and strict legal market environment. •Negative correlation between industrial concentration and pollutants was clarified.•Inverted pyramid sharply reflects the relationship between firm size and pollutant emissions.•Unified market environment prevents pollution transfer in structure upgrade process.